Optimization of the Lipase-Catalyzed Selective Amidation of Phenylglycinol - Sun, Meina; Nie, Kaili; Wang, Fang; Deng, Li (Frontiers in Bioengineering and Biotechnology, 2020)
Ceramides and their analogues have a regulatory effect on inflammatory cytokines expression. It was found that a kind of ceramides analogue synthesized from phenylglycinol could inhibit the production of cytokine TNF-α. However, two active hydrogen groups are present in the phenylglycinol molecule. It is difficult to control the process without hydroxyl group protection to dominantly produce amide in the traditional chemical synthesis. A selective catalytic the amidation route of phenylglycinol by lipases was investigated in this research. The results indicated that the commercial immobilized lipase Novozym 435 has the best regio-selectivity on the amide group. Based on the experimental results and in silico simulation, it was found that the mechanism of specific N-acyl selectivity of lipase was not only from intramolecular migration and proton shuttle mechanism, but also from the special structure of active site of enzyme. The optimal reaction yield of aromatic amide compound in a solvent-free system with lipase loading of 15 wt% (to the weight of total substrate) reached 89.41±2.8% with very few of byproducts detected (0.21±0.1% ester and 0.64±0.2% diacetylated compound). Compare to other reported works, this work have the advantages such as low enzyme loading, solvent free, and high N-acylation selectivity. Meanwhile, this Novozym 435 lipase based synthesis method has an excellent regio-selectivity on most kinds of amino alcohol compounds. Compared to the chemical method, the enzymatic synthesis exhibited high regio-selectivity and conversion rates. The method could be a promising alternative strategy for the synthesis of aromatic alkanolamides.